Struggling with Cultural Integration: Elementary Teachers’ Efforts to Incorporate the Javanese Calendar in Teaching Plan - Niken Wahyu Utami; Sagita, Laela; Rina Dyah Rahmawati (Mathematics Education Journal, 2025)
Although the mathematical potential of Javanese calendar has been widely explored, little is known about the challenges teachers face in its classroom integration. This study addresses the gap to inform effective instructional design. This research aims to identify the challenges teachers encounter in developing culture-based mathematics teaching plan. A questionnaire was distributed to a group of elementary school teachers participating in the Culture-Based Pedagogy course in the Master Program of Basic Education at a university in Yogyakarta. A total of 44 elementary school teachers completed the questionnaire. Based on the results of the learning plans they prepared, five teachers were selected for in-depth interviews. Data were analyzed descriptively, focusing on the teachers’ lesson plans and interview responses. The findings indicate that teachers’ integration of the Javanese calendar was multifaceted, encompassing their mathematical and cultural knowledge as well as their pedagogical skills during the lesson planning process. The analysis revealed three distinct patterns of integration. First, the Javanese calendar was thoughtfully integrated into the lesson plans, providing rich opportunities for contextual repurposing across various themes. Second, the lesson plans used superficial or tokenistic references where culture is included only as a decorative element without a meaningful link to the learning objectives. Third, in the problematic case, the lesson plans were used in inauthentic cultural contexts, resulting in cultural misconceptions. It is suggested that a comprehensive guide for educators be developed, encompassing meticulous explanations, precise calculations, and culturally pertinent information, particularly concerning the Javanese calendar. Additionally, the provision of further training or mentoring is considered essential for developing appropriate lesson designs.